Long‐term incidence of upper extremity venous obstruction in implantable cardioverter defibrillator patients. Issue 6 (24th May 2021) - Horlbeck, Fritz W.; Eckerth, Christopher; Linhart, Markus; Schaefer, Christian; Jakob, Mark; Pingel, Simon; Klarmann‐Schulz, Ute; Nickenig, Georg; Schwab, Joerg O.
Abstract: Background: Very little is known about the long‐term prevalence of severe venous obstruction and occlusion in patients with transvenous implantable cardioverter‐defibrillator leads. The objective of the current investigation was to elucidate the incidence and prevalence and to identify predisposing conditions in an ICD cohort over a long follow‐up period. Methods: Based on a prospective database, we analyzed consecutive patients who received an ICD implantation in our hospital between 06/1988 and 2009 as well as all corresponding follow‐up data until 02/2018. Cavographies were used for analysis, and all patients with at least one device replacement and one follow‐up cavography were included. Results: Over a mean follow‐up period of 94 ± 50 months, severe venous obstruction was found in 147 (33%) of 448 patients. Kaplan‐Meier analysis shows a severe obstruction or occlusion in 50% of patients after a period of 14.3 years. The total number of leads ( p < .001, HR 2.01, CI 2.000–2.022), an advanced age ( p = .004, HR 1.023 per year, CI 1.022–1.024) and the presence of dilated cardiomyopathy ( p = .035, HR 1.49, CI 1.47–1.51) were predictive of venous obstruction whereas the presence of anticoagulation was not. Conclusion: Severe obstruction of the access veins after ICD implantation occurs frequently and its prevalence shows a nearly linear increase over long‐time follow‐up. Multiple leads, an advanced age and DCM as underlying disease are associated with an increased risk of venous obstruction while the role of anticoagulation to prevent venous obstruction in ICD patients is unclear.